Effects of Polymethylmethacrylate Cement Viscosity and Bone Porosity on Cement Leakage and New Vertebral Fractures After Percutaneous Vertebroplasty: A Prospective Study - Alhashash, Mohamed (Global Spine J, 2019)
STUDY DESIGN: A prospective randomized study. OBJECTIVES: To evaluate the effect of bone cement viscosity as well as of bone porosity on cement leakage during vertebroplasty and to analyze the occurrence of new vertebral fractures after the procedure. METHODS: Between April 2012 and December 2013, 60 patients suffering from osteoporotic vertebral fractures underwent vertebroplasty. The patients were randomly assigned into 2 equal groups. High-viscosity cement was used in group A, while low-viscosity cement was used in group B. Patients were followed-up for a minimum of 2 years. RESULTS: Cement leakage occurred in 16 patients in group B (20 vertebral bodies) and in 6 patients in group A (9 vertebral bodies). The difference was statistically significant (χ(2) = 2.3, P = .01). Lower T-scores were associated with significantly more cement leakage (t = 3.338, P = .002 in group A, and t = 4.329, P = .000 in group B). Patients with a T-score worse than −1.8 had a significantly higher risk of cement leakage if low-viscosity cement was used (χ(2) = 3.25, P = .05). New vertebral fractures occurred in 14 (23%) patients, after a mean of 6.5 ± 5.5 months, 10 patients in group A and 4 in group B. The difference did not reach the statistical significance level (χ(2) = 3.354, P = .067). Patients presenting with multiple fractures had a significantly more number of new vertebral fractures (χ(2) = 7.464, P = .006). CONCLUSIONS: The clinical outcome of vertebroplasty was not influenced by cement viscosity. However, lower cement viscosity and higher degree of osteoporosis were found to be significant risk factors for cement leakage. Furthermore, the number of vertebral body fractures on presentation was a predictor for the occurrence of new fractures postoperatively.